Kong Konstantin og det græske oberststyre - Pelt, Mogens (Historisk Tidsskrift, 2013)
King Constantine and the Greek ColonelsPolitical power in post-war Greece was exercised by three institutions: the Army, the Palace, and the Government. At certain junctures American influence played a significant role. It should be noted that Army and Palace influence has a long history in Greek politics. This article focuses on the relations between King Constantine II and the armed forces prior to the military coup d’etat on 21 April 1967 and during the Colonels’ regime. It also touches the period after the collapse of military rule in Greece. The article is mainly based on official US documents, particularly on material from the desk of Charilaos Lagoudakis, the Greek analyst in the Bureau of Intelligence and Research in the State Department.Constantine ascended to the throne on 6 March 1964 in a political situation dominated by an increasingly bitter struggle between the government on one hand and the Palace and the armed forces on the other. Constantine’s coronation took place less than a year after his father, King Paul, had emerged victorious from a conflict with his prime minister, the conservative but independent Constantine Karamanlis, forcing the latter to resign. According to American sources Queen Frederika in particular but also Crown Prince Constantine preferred to keep Karamanlis out of power. Their motives were believed to include an ardent dislike of a strong prime minister who had deserted the royal cause.In 1964 George Papandreou of the Centre Union won two consecutive elections and became prime minister. Papandreou’s intentions to dismantle certain features of the previous right-wing system and his attempts to bring the armed forces under political control prompted the Palace and the Army to unite. Following the forced resignation of Papandreou in 1965, Constantine sought ways to prevent Papandreou’s return to power. This process seemed to include preparations for a military take-over. The King endorsed contingency planning within the army, and by the end of 1966 a coup d’etat could be activated at any time on his order. On 20-21 April 1967 this planning enabled the Colonels to snatch command from Constantine and the senior officers and carry out the take-over themselves. The Colonels made their decision to move when it appeared that the generals and the King were still vacillating. However, when confronted with the Colonels’ fait accompli the Chief of the General Staff decided to join the new regime. The King accepted the new regime, albeit reluctantly.The relationship between the King and the Colonels had strong elements of friction and soon developed into a power struggle. In the process the King steadily lost ground, and in December 1967 he launched a coup d’etat which proved abortive. He then fled Greece and settled in Rome, later in England. The King wanting to regain his position obviously needed the Colonels more than they needed him. Between 1969 and 1972 Constantine tried to influence the US to persuade the Colonels to accept his return to Greece. Eventually the King declared himself ready to accept a government under the leadership of the regime’s strong man, George Papadopoulos, but in vain. The Junta - and the Americans - had other plans, and from 1972 onwards the regime worked openly to undermine Constantine’s public stature in Greece. In May 1973 an abortive mutiny in the Greek navy offered Papadopoulos an opportunity to abolish the Monarchy on 1 June 1973.After the collapse of the military regime Constantine obviously hoped to return to Greece. However, in the new situation he had to rely on the politicians and popular support and failed utterly. A referendum on 8 December 1974 decided by a majority of c. 70 % to abolish the Monarchy. The issue of his lost crown seems to have dominated the dethroned King’s relations to Greek political life to such a degree that he appeared a potential ally to people planning to install a new unconstitutional regime and undo the changes after the fall of the Junta.King Constantine’s driving motivation prior to the 1967 coup seems to have been a marked aversion against a strong government based on popular support and beyond the control of the Palace and the Army. During the Colonels’ regime and early post-Junta years his main efforts were to save the Crown.